Leptin Intake at Physiological Doses Throughout Lactation in Male Wistar Rats Normalizes the Decreased Density of Tyrosine Hydroxylase-Immunoreactive Fibers in the Stomach Caused by Mild Gestational Calorie Restriction - Szostaczuk, Nara; Sánchez, Juana; Konieczna, Jadwiga; Palou, Andreu; Picó, Catalina (Frontiers in Physiology, 2018)
Introduction: Gestational under nutrition in rats has been associated with lower expression of sympathetic innervation markers in offspring, affecting peripheral tissues such as the stomach. This has been linked to lower gastric secretion and decreased circulating levels of ghrelin. Considering the critical role of leptin intake during lactation to prevent obesity and reverse developmental malprogramming effects, we aimed to assess whether leptin supplementation may reverse the above mentioned alterations caused by mild gestational calorie restriction. Methods: Three groups of male rats were studied at a juvenile age (25 days old) and during adulthood (3 and 6 months old): the offspring of ad libitum fed dams (controls), the offspring of dams that were diet restricted (20%) during the first part of pregnancy (CR), and CR rats supplemented with a daily oral dose of leptin (equivalent to 5 times the average amount they could receive each day from maternal milk) throughout lactation (CR-Leptin). Tyrosine hydroxylase (TyrOH) levels and the density of TyrOH-immunoreactive (TyrOH+) fibers, used as potential markers of functional sympathetic innervation, were measured in the stomach. Plasma leptin and ghrelin levels were determined. Results: At 25 days, CR rats displayed lower density of TyrOH+ fibers (-46%) and lower TyrOH levels (-47%) in the stomach than controls. These alterations were not found in CR-Leptin animals. Alterations in CR animals were mitigated at the age of 6 months, and differences were not significant. Adult CR-Leptin animals showed higher plasma ghrelin levels than CR animals, particularly at 3 months (+16%), and a lower leptin/ghrelin ratio (-28% and -37% at 3 and 6 months, respectively). Conclusion: Leptin intake during lactation is able to reverse the alterations in the density of TyrOH+ fibers in the stomach and normalize the increased leptin/ghrelin ratio linked to a mild gestational calorie restriction in rats, supporting the relevance of leptin as an essential nutrient during lactation.